Human model of burn injury that quantifies the benefit of cooling as a first aid measure. Issue 11 (23rd August 2019) - Wright, E. H.; Tyler, M.; Vojnovic, B.; Pleat, J.; Harris, A.; Furniss, D.
Abstract : Background: Burn injuries are a major cause of morbidity and mortality worldwide. Cooling is widely practised as a first aid measure, but the efficacy of cooling burns in human skin has not been demonstrated. A safe, consistent, ethically acceptable model of burning and cooling in live human skin in vivo was developed, and used to quantify the effects of cooling. Methods: Novel apparatus was manufactured to create and cool burns in women who were anaesthetized for breast reconstruction surgery using a deep inferior epigastric artery perforator flap. Burns were excised between 1 and 3 h after creation, and analysed using histopathological assessment. Results: All 25 women who were approached agreed to take part in the study. There were no adverse events. Increased duration of contact led to increased burn depth, with a contact time of 7·5 s at 70°C leading to a mid‐dermal burn. Burn depth progressed over time following injury, but importantly this was modified by cooling the burn at 16°C for 20 min. On average, cooling salvaged 25·2 per cent of the dermal thickness. Conclusion: This study demonstrated the favourable effects of cooling on human burns. Public heath messaging should emphasize cooling as first aid for burns. This model will allow analysis of the molecular effects of cooling burns, and provide a platform for testing novel therapies aimed at reducing the impact of burn injury. Abstract : An ethically acceptable human model of burn injury was created and used to demonstrate the effectiveness of cooling in reducing the depth of burn injury. This model can be used to investigate the effects of burning and cooling on human skin, and to test new treatments for burn injury. Reliable model Abstract : Antecedentes: Las lesiones por quemadura son una causa importante de morbilidad y mortalidad en todo el mundo. El enfriamiento de las quemaduras se practica ampliamente como medida de primeros auxilios, pero no se ha demostrado su eficacia en la piel de los seres humanos. Para cuantificar los efectos del enfriamiento, se desarrolló un modelo de quemadura y enfriamiento en piel humana in vivo, seguro, estable y éticamente aceptable. Métodos: Se construyó un dispositivo nuevo para crear y enfriar quemaduras en pacientes que fueron anestesiadas para una reconstrucción mamaria utilizando un colgajo perforante de la arteria epigástrica inferior profunda. Las quemaduras se extirparon entre una y tres horas después de su producción y se analizaron por evaluación histopatológica. Para determinar la significación estadística entre grupos se utilizó las pruebas de ANOVA o de t pareadas, según correspondiera. Resultados: Aceptaron participar en el estudio las 25 pacientes a las que se propuso. No hubo efectos adversos. La mayor duración del contacto conllevó un aumento en la profundidad de la quemadura: con un tiempo de contacto de 7, 5 segundos a 70°C se obtuvo una quemadura dérmica de segundo grado. La profundidad de la quemadura aumentó con el tiempo de exposición, pero mejoró de forma sustancial al enfriar la quemadura a 16°C durante 20 minutos. El enfriamiento salvó el 25% del espesor dérmico como promedio. Conclusión: Este es el primer estudio que demuestra los efectos favorables del enfriamiento sobre las quemaduras humanas. Los consejos de salud deberían hacer más énfasis en el enfriamiento como forma de primeros auxilios en las quemaduras. Este modelo permitirá identificar los efectos moleculares del enfriamiento en las quemaduras y proporcionará una plataforma para probar nuevos tratamientos encaminados a reducir el impacto de las lesiones por quemadura.